Distorsi Hukum Penggunaan Teknik Undercover Buy dalam Tindak Pidana Narkotika oleh Penyidik Kepolisian Republik Indonesia - Annisa, Febrina; Gustaliza, Resma Bintani; Palupi, Dwi Astuti; Putri, Prima Resi; Rosra, Deswita (Nagari Law Review, 2023)
Drug crime is one of the proxy war weapons that can destroy a nation by targeting the younger generation. Indonesia is one of the countries with a high level of trafficking and Use of drugs. To tackle drug crime, the Indonesian government drafted the Law Number 35 of 2009 concerning Drugs. At first glance, the authority of investigations in the Drugs Law seems to be under the order of the National Narcototices Board of Indonesia (BNN) and the Police of the Republic of Indonesia (Polri). However, if we take a closer look, there are some problems in investigations, especially in Undercover Buy and Controlled Delivery techniques regulated in Article 75 Letter J of the Drugs Law. This problem can lead to legal distortion in investigating drug crime by the Polri because it can be categorized as procedural defects due to the law. Hence, this study aims to analyze the legal distortion of authority between BNN and Polri to investigate drug crime using undercover buying techniques. This study also analyses the statutory provisions that can provide legal certainty for both government institutions so that the authorities of Polri and BNN do not overlap. This study finds that only BBN investigators have the authority to use undercover buying and controlled delivery. Therefore, using the technique by the police investigator will cause legal distortion. If the police investigator needs to use the technique, there should be a legal basis. Therefore, there should be an amendment to the Narcotic law to provide the legal basis.